Health status and negotiability for medical care reserve officers and retired officers - O E Konovalov; A V Popov; A V Breusov (RUDN Journal of Medicine, 2016)
In the course of the present study were conducted sociological survey 574 reserve officers and retired officers. Despite the relatively high subjective assessment of the health of the respondents they had different complaints about their state of health. These were mainly complaints of violations on the part of the circulatory system, musculoskeletal system, digestive organs and organs of sense (sight, hearing). Incidence rate was 203.9 per 100 respondents. At the same time at everyone were registered from 1 to 4 diseases, an average per person accounted for 2.13 of the disease. The analysis showed that there was a direct correlation of medium strength between the quantity of disease and the availability of disability in patients. It was found that 84% of respondents sought medical care at least once a year, and among them, 22.1% - at least once a half year. Nearly one-third (29.8%) of former military have transferred serious illness, injury and surgery operations. Over the past year 85.4% of respondents called for an ambulance, among them 23.5% did so every month.